Effect of soluble factors of macrophages polarized by efferocytosis on neuronal density in the frontal cortex and hippocampus of mice in a model of stress-induced depression - I. M. Rashchupkin; T. G. Amstislavskaya; E. V. Markova; A. A. Ostanin; E. Ya. Shevela (Медицинская иммунология, 2023)
Recently, there has been a steady increase in depressive disorders, which occupy an important place in the structure of the causes of disability. In the pathogenesis of depression, an important role is played by neuroinflammation, which is associated with impaired adult neurogenesis. Notably, neuroinflammation is partially reversible, and the leading role in the initiation and regulation of neuroregeneration is given to macrophages. Opposite states of macrophage activation are classically activated M1 and alternatively activated M2 macrophages, characterized, respectively, by pro- and anti-inflammatory activity. A balance shift towards M2 macrophages has been considered as a new therapeutic strategy of psycho-neurological disorders. One of the inducers of the M2 phenotype is the efferocytosis. We have previously developed an original protocol for the generation of human macrophages under conditions of deficiency of growth / serum factors, in which M2 phenotype is formed through efferocytosis. Macrophages (M2(LS), LS – Low Serum) obtained according to this protocol express M2-associated markers, and are characterized by high production of growth and pro- angiogenic factors (IGF-1, VEGF, BDNF, EGF, FGF-basic, etc.), which can suppress inflammation and stimulate neuroregeneration / neuroplasticity. In the model of stress-induced depression, the antidepressant effect of soluble factors of M2(LS) macrophages was shown, accompanied by a decrease in the level of pro- inflammatory cytokines in certain brain structures. However, the effect of M2(LS) factors on neurogenesis remained unexplored. In the present work, which is a continuation of the aforementioned study, we analyzed the effect of intranasal administration of M2(LS) soluble factors on neuronal density in different brain areas – the frontal cortex and hippocampus – of depression-like mice. The results obtained showed that neuronal density in the frontal cortex, CA1 and CA3 zones of the hippocampus, was significantly higher in mice with intranasal administration of M2(LS) conditioned medium than in depression-like mice, and reached the level of neuronal density in intact animals. These results may indicate the neuroregenerative activity of M2(LS) macrophages in the model of stress-induced depression, which is mediated through soluble factors and manifests itself in an increase in the density of neurons in the brain.